Differentiation of the XY Sex Chromosomes in the Fish Hoplias malabaricus (Characiformes, Erythrinidae): Unusual Accumulation of Repetitive Sequences on the X Chromosome - Cioffi, M. B.; Martins, C. [UNESP]; Vicari, M. R.; Rebordinos, L.; Bertollo, L. A. C. (Karger, 2010)
The wolf fish Hoplias malabaricus (Erythrinidae) presents a high karyotypic diversity, with 7 karyomorphs identified. Karyomorph A is characterized by 2n = 42 chromosomes, without morphologically differentiated sex chromosomes. Karyomorph B also has 2n = 42 chromosomes for both sexes, but differs by a distinct heteromorphic XX/XY sex chromosome system. The cytogenetic mapping of 5 classes of repetitive DNA indicated similarities between both karyomorphs and the probable derivation of the XY chromosomes from pair No. 21 of karyomorph A. These chromosomes appear to be homeologous since the distribution of (GATA)(n) sequences, 18S rDNA and 5SHindIII-DNA sites supports their potential relatedness. Our data indicate that the differentiation of the long arms of the X chromosome occurred by accumulation of heterochromatin and 18S rDNA cistrons from the ancestral homomorphic pair No. 21 present in karyomorph A. These findings are further supported by the distribution of the Cot-1 DNA fraction. In addition, while the 18S rDNA cistrons were maintained and amplified on the X chromosomes, they were lost in the Y chromosome. The X chromosome was a clearly preferred site for the accumulation of DNA repeats, representing an unusual example of an X clustering more repetitive sequences than the Y during sex chromosome differentiation in fish. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Cot-1 DNA; Fishes; Heterochromatin accumulation; Molecular cytogenetics; Repetitive DNA; Sex chromosome differentiation